2014
DOI: 10.1155/2014/271061
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of a Portable Sleep Monitor to Diagnose Sleep‐Disordered Breathing in a Pediatric Population

Abstract: Although PSG is still recommended for the diagnosis of SDB, the ApneaLink sleep monitor has a role for triaging children referred for evaluation of SDB, but has limited ability to determine the nature of the SDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
(29 reference statements)
1
31
1
Order By: Relevance
“…In the present study, we observed that HPG overestimated AHI compared with the PSG, similar to Massicotte et al and incorrectly diagnosed patients with OSAS. The over‐diagnosis of OSAS with polygraphy may be due to events scored during wakefulness, reduced flow observed on a nasal flow channel during mouth breathing even in the absence of apnea and/or post‐arousal artifacts mistaken as reduced airflow.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we observed that HPG overestimated AHI compared with the PSG, similar to Massicotte et al and incorrectly diagnosed patients with OSAS. The over‐diagnosis of OSAS with polygraphy may be due to events scored during wakefulness, reduced flow observed on a nasal flow channel during mouth breathing even in the absence of apnea and/or post‐arousal artifacts mistaken as reduced airflow.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study by Rosen et al a subgroup of 55 children in the study group had in‐lab PSG and HPG performed within 3 months for comparison, and when using an AHI ≥ 5/h total sleep time (TST) as cut‐off for the diagnosis of OSAS, the sensitivity of HPG was 88% and the specificity was 98%. Massicotte et al studied 35 children with PSG and polygraphy simultaneously in the sleep lab and using a cut‐off AHI ≥ 1.5 events/h, the manually scored polygraphy had a sensitivity of 94% and specificity of 16% to detect OSAS (AHI ≥ 1.5 events/h) diagnosed by PSG. When the cut‐off was increased (AHI of ≥5 events/h) polygraphy still had good sensitivity of 94% and specificity increased to 61% in detecting OSAS (AHI ≥ 1.5 events/h) diagnosed by PSG.…”
Section: Discussionmentioning
confidence: 99%
“…Although some data have been published to support the ability of the ApneaLink™ to make this distinction [20], portable SDB screening tests overall are not considered to provide reliable assessments of obstructive versus central etiologies [21,22]. Further, SDB after stroke is known to be predominantly (94%) obstructive in nature [23].…”
Section: Methodsmentioning
confidence: 99%
“…Breathing disorders were assessed using a specific and light device ApneaLink ® (ResMed Germany Inc., ref 22301) in all study sites, allowing a non‐invasive measurement of respiratory parameters. This device has been previously described and used in several studies for identification of sleep apnea in patients 18, 19, 20. Briefly, ApneaLink ® is a single‐channel screening device that measures airflow through a simple nasal cannula connected to a pressure transducer, providing an apnea‐hypopnea index (AHI) based on recording time 18.…”
Section: Methodsmentioning
confidence: 99%